07.17: Design methods for drive‐in steel storage racks. (13th September 2017) - Shaheen, Mahmoud S.A.; Rasmussen, Kim J.R.
ABSTRACT: The European racking federation design guidelines FEM10.2.07 (2012) contains provisions for the analysis and design of drive‐in and drive‐through racks. It specifies different methods for carrying out the design, and the design verifications differ depending on the method chosen. However, there appears to be no published studies that compare the analysis and design methods specified in FEM10.2.07 and give recommendations for using a particular method over the other. In addition, the design guidelines are unclear about the definition of the effective length to use in the design of uprights. Depending on the way the effective length provisions are interpreted it leads to significantly different solutions. This paper studies the different design methods specified in FEM10.2.07 and exemplifies the differences, advantages and disadvantages of each method, and puts forward recommendations for design depending on drive‐in rack characteristics.